EVALUATION OF ANCIENT MANUSCRIPT PRESERVATION AT THE MPU TANTULAR STATE MUSEUM - Ramadhani, Firasya Salsabila; Syahri, Moch (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Many ancient manuscripts in Indonesia are experiencing damage, neglect, and even illegal trade, endangering their status as cultural heritage. The Mpu Tantular State Museum, which houses 334 manuscripts, plays a crucial role in safeguarding these collections. However, a comprehensive evaluation of its preservation practices has never been conducted. This study aims to evaluate the preservation of ancient manuscripts at the Mpu Tantular State Museum using the CIPP (Context, Input, Process, Product) evaluation model. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews with three key informants, and documentation. Source triangulation was conducted through policy documents, activity reports, and field observations to ensure data validity. The results show that in the context aspect, the museum has established clear objectives and supporting policies, although a structured evaluation system is lacking. In terms of input, limitations remain in human resources, facilities, and budget allocation. The preservation process is conducted through traditional yet systematic methods, such as cleaning, citronella oil application, and fumigation, supported by external collaboration. The product aspect demonstrates positive outcomes in maintaining manuscript condition and academic utilization, although public access remains limited. Theoretically, this study contributes to expanding the application of the CIPP model in the field of manuscript preservation by adapting it to the context of regional museums, offering a new analytical perspective that bridges the gap between ideal preservation standards and practical implementation in local cultural institutions.